Rig ʼdzin grub paʼi dbaṅ phyug chen po Padma ʼbyuṅ gnas kyi rnam par thar pa ṅo mtshar phun sum tshogs paʼi rgya mtsho: a detailed account of the life of Guru Rimpoche Padmasambhave miraculously born - Bkra-śis-stobs-rgyal, Byaṅ-bdag, 16th cent (Sherab Gyaltshen Lama, 1976)
Detailed life of the Indian spiritual master, Padmasambhava, ca. 717-762.